The Effect of Flexible Resin and Standard Resins Mixtures Variations on Dimensional Accuracy Using SLA 3D Printing - Dyaksa, Gilang Argya; Aji Nugraha, Felix Krisna; Astyanto, Achilleus Hermawan; Mardikus, Stefan; Seen, Michael; Rines, Rines; Lukiyanto, Yohanes Baptista; Purwadianto, Doddy; Winarbawa, Heryoga; Kusbandono, Wibowo; Sugiharto, Budi; Hermawan, Oktavianus Nekson; Putra, Mahendra Pratama (International Journal of Applied Sciences and Smart Technologies, 2025)
The present study investigates the effect of the concentration of flexible resin on the dimensional accuracy of mixtures product manufactured by 3D printing using SLA technology. Specimens were designed and according to the ASTM D412 standard. Ten variations of resin mixtures were examined. The concentrations of the flexible resins were varied from 10% to 100%. Measurements of accuracy dimension were conducted on the fabricated specimens, and the average deviation was used to estimate the dimensional accuracy. The study reveals the least deviation in dimensions in the 10% flexible resin containing mixture and the highest in the 60% flexible resin containing mixture. The results explain the fabrication tendency of flexible resins in dimensional accuracy for 3D printing.